Slavistična vrstnika Miklošič in Sreznjevski v Jagićevi osvetlitvi - Jakopin, Franc (Slavistična revija, 1997)
Franc Mikološič's Slavic scholarship in Vienna coincides with the work of his contemporary Izmail I. Sreznevsky in St. Petersburg. In the second half of the 19th c. both philologists and both centers were major importance for the development of the Slavic scholarship. The author comparatively analyzes Jagić's explanation of philological and linguistic achivements by both of his immediate predcessors at their respective Slavic chairs in St. Petersburg and Vienna.
Keywords: 19.st.; Jagić, Vatroslav, 1838-1923; jezikoslovci; jezikoslovje; linguistics; Miklošič, Fran, 1813-1891; slavisti; Sreznjevski, Izmail I., 1812-1880